قياس درجة السلوك الفوضوي لدى عينة من تلاميذ الصف السابع الأساسي في مدارس محافظة درعا - الغزالي، أحمد قاسم; الزحيلي، غسان محمود (جامعة دمشق, 2022)
هدف البحث الحالي إلى تعرف درجة السلوك الفوضوي التي يواجهها تلاميذ الصف السابع الأساسي في مدارس محافظة درعا (أفراد عينة البحث)؛ ولتحقيق هذا الهدف صمم الباحث (مقياس السلوك الفوضوي)، والذي تكون من (46) فقرة تشتمل على أربعة أبعاد هي: (الإثارة والإزعاج- العدوان- التخريب- مخالفة الأنظمة والتعليمات المدرسية). وتكونت عينة البحث من (1530) تلميذا وتلميذة من تلامذة الصف السابع الأساسي في مدارس محافظة درعا. وقد توصل البحث إلى أن درجة السلوك الفوضوي لدى تلامذة الصف السابع الأساسي في مدارس محافظة درعا (أفراد عينة البحث) من وجهة نظرهم كانت بدرجة (مرتفعة) وبمتوسط حسابي قدره (2.94)، وبانحراف معياري قدره (.619). كما تبين أن ليس هناك أية فروق ذات دلالة إحصائية بين تلامذة الصف السابع الأساسي في مدارس محافظة درعا (أفراد عينة البحث) في مقياس السلوك الفوضوي وفقا لمتغيري (الجنس- الترتيب الولادي للطالب). وفي ضوء النتائج السابقة قدم البحث بعض المقترحات التي يمكن تداولها لتخفيض درجة السلوك الفوضوي لدى تلامذة الصف السابع الأساسي في مدارس محافظة درعا. The current research aimed to identify the degree of anarchic behavior that primary seventh-grade students face in Daraa governorate schools (individuals of the research sample). To achieve this goal, the researcher designed the (Anarchic Behavior Scale), which consisted of (46) paragraphs that include four dimensions:(agitation and disturbance aggression- sabotage- violation of school rules and instructions). The research sample consisted of (1530) male and female students of the seventh grade in the schools of Daraa governorate. The research found that the degree of anarchic behavior among seventh grade students in the basic schools of Daraa Governorate (members of the research sample) from their point of view was (high) with a mean of (2.94), and a standard deviation of (.619). It was also found that there are no statistically significant differences between the seventh grade students in the schools of Daraa governorate (individuals of the research sample) in the measure of anarchic behavior according to the variables (gender- the birth order of the student in the family). In light of the previous results, the research presented some proposals that could be negotiated to reduce the degree of anarchic behavior among seventh grade students in the schools of Daraa governorate.
Keywords: التعليم الأساسي -- طلبة التعليم الأساسي -- الصحة النفسية -- السلوك الفوضوي -- مدارس محافظة درعا